3D In2S3/C/Fe3C nanofibers for Z-scheme photocatalytic CO2 conversion to acetate - Chen Liao; Wenhao Jing; Feng Wang; Ya Liu (Materials Today Catalysis, 2023)
Constructing a Z-scheme heterostructure is of great significance to achieve efficient photocatalytic CO2 conversion without sacrificial reagents. However, the fabrication of a well-suited Z-scheme remains a challenge. In this work, we constructed a Z-scheme system with a suitable band structure by in-situ hydrothermal growth of In2S3 nanosheets on electrospun Fe3C/Carbon fibers with 3D structure. The Z-scheme electron transport path is verified by the calculation of the energy band structure calculation and the method of photodeposition, indicating that In2S3 and Fe3C are reduction reaction sites and oxidation reaction sites respectively. Carbon fibers serve as both the skeleton of the 3D structure and the electron mediator from Fe3C to In2S3. Moreover, the DFT calculation demonstrates that the introduction of Fe3C can reduce the energy barrier of *CO and *COH coupling on In2S3, and weaken the bonding of In-S, thereby enhancing the product selectivity towards acetate. Owing to the efficient charge transfer of the Z-scheme system, the photocorrosion in In2S3 is also greatly reduced, showing a relatively stable chemical composition after several hours of reaction. Compared with In2S3 and Fe3C/C, In2S3-C/Fe3C composites showed a significantly increased acetate evolution rate of 11.33 μmol/h/g without any sacrificial reagents. This work provides important insights into the design and research of the photocatalyst system that combines a monolithic 3D structure and a Z-scheme charge flow for efficient CO2 conversion.